Preparation method and device of compact uranium-containing sandstone artificial core

By using the method of dual temperature and pressure control and gas reaction in the preparation of artificial sandstone cores, problems such as simple equipment, unreal diagenetic process, and large composition differences in the prior art were solved, and artificial cores with stable properties and diverse compositions were prepared to simulate the fluid flow mechanism and ground leach mining process in the uranium ore reservoir.

CN119880549AActive Publication Date: 2025-04-25INST OF ROCK & SOIL MECHANICS CHINESE ACAD OF SCI

Patent Information

Application Number
CN202510027418.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-25
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The existing artificial sandstone core preparation technology has problems such as the device being too simple or complex and expensive, the diagenetic process without first compaction and then cementation, the addition of multiple chemical substances leads to large differences in the components and unstable properties, which limits the research and development of uranium mineral resource exploration and development technology.

Method used

A method for preparing a dense uranium-containing sandstone artificial core is adopted. By mixing quartz sand with feldspar with different particle sizes, adding clay, uranium-containing minerals and calcium hydroxide powder, and after thorough mixing, it is heated and pressurized in a core mold with dual control of water spray wetting and temperature pressure, injecting water and gas for reaction, simulating the rock formation process, and finally, artificial cores that meet the requirements are prepared by adjusting the temperature, pressure and gas-liquid injection volume.

Benefits of technology

An artificial core with stable properties, diverse compositions, diagenesis, pore throat structure and mechanical properties are similar to that of natural cores. It can be used to simulate the fluid flow mechanism and ground leach mining process in the dense sandstone-type uranium ore reservoir, providing reliable experimental support.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119880549A_ABST
    Figure CN119880549A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a compact uranium-containing sandstone artificial core, which comprises the following steps: mixing quartz sand and feldspar with different particle sizes, adding clay, uranium-containing minerals and calcium hydroxide powder, and mixing; spraying water for wetting, stirring and cooling to room temperature; adding the mixed system into a rock core mold, raising the temperature and pressure, injecting a small amount of preheated water, and keeping constant temperature and constant pressure for reaction; sequentially introducing carbon dioxide and hydrogen sulfide gas into the core mold for at least three times, and collecting and metering the amount of gas and liquid which do not participate in the reaction; cooling and depressurizing, drying, and metering the gas-liquid amount participating in the reaction; evaluating the pressure, the temperature and the pH value of the reaction, and adjusting the pressure, the temperature and the gas-liquid injection amount until a sample similar to the diagenetic environment of the natural compact uranium-bearing sandstone is obtained. According to the invention, the hydrothermal fluid injection process in the uranium-bearing sandstone diagenesis process and the deposition compaction, cementation, excursion and corrosion diagenesis effects can be truly simulated; and further preparing the compact uranium-containing sandstone artificial core with physical property parameters meeting requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of uranium mine exploration and development, and in particular to a method and a device for preparing a dense uranium-containing sandstone artificial core. Background Art

[0002] As a stable and clean energy, nuclear energy has the advantages of being green, low-carbon, stable in power supply, and high in energy density. Uranium resources, as an important raw material for the development of nuclear power, play a vital role in energy resource security. At present, sandstone-type uranium deposits, as the main type of uranium resources, are receiving more and more attention. Artificial core physical simulation is one of the important means to solve scientific research tasks in the process of uranium resource exploration and development, and a large number of cores are required during the entire research period.

[0003] Sandstone-type uranium deposits are often characterized by deep burial, low permeability, dense pores, and high cementation of reservoirs. Conventional drilling and coring methods are costly and weak, and cannot be used to study the occurrence state of uranium ore in the reservoir, pore structure, permeability evolution, and fluid flow mechanism. Therefore, it is imperative to develop artificial dense uranium-containing sandstone to provide experimental support for uranium exploration and development technology research. In addition, in-situ leaching uranium technology in sandstone-type uranium deposits has become the main method for natural uranium production at home and abroad. Using repeatable artificial cores to study the changes in the micropore structure inside the reservoir during in-situ leaching of uranium and the inversion of the seepage process of the leaching solution can provide technical support for improving the leaching effect of uranium ore.

[0004] Chinese patent CN107144452A discloses a method for preparing a shallow loose oil-bearing artificial sandstone core of Guantao Formation, wherein the loose sandstone of the target layer is ground into powder by a ball mill, and then sand samples of different particle sizes are screened out with a standard test sieve, and then the sand samples of different particle sizes are weighed and mixed evenly, and then the mixed sand samples, the binder added with acetone, and the emulsified oil are mixed and stirred evenly until there are no larger particles, and then loaded into the core preparation mold, and the pressure is pressed and formed by a hydraulic jack, and finally sealed with tin foil and placed in a cool place to dry naturally, thereby obtaining an oil-bearing artificial sandstone core. The method is simple in process, low in cost, and the pore structure is close to that of a natural core. However, the method does not undergo a high temperature and cemented diagenetic process, and the addition of a variety of chemical substances causes the composition difference from the real rock sample to be too large.

[0005] Chinese patent CN104931312A discloses a temperature-pressure dual-control dense artificial sandstone core and a preparation method thereof, in which 100g-200g of quartz sand with a particle size of 300-500 mesh is mixed in 100mL-150mL of water, and the temperature is raised to 300℃-350℃, the pressure is raised to 220MPa-250MPa, the temperature and pressure are kept constant for 15h-20h, the temperature and pressure are lowered to room temperature and atmospheric pressure, and the sample is taken out to obtain a temperature-pressure dual-control dense artificial sandstone core. The core prepared by this invention has a high degree of similarity in overall pore structure with the pore structure of real geological samples. However, the composition of the core prepared by this method is different from that of real sandstone, and there are problems of high cost and long production cycle.

[0006] Chinese patent CN103880384A discloses an artificial sandstone core, preparation method and use, which is mainly prepared from the following raw materials according to the weight percentage of each component: clay 220%, cement 5-25%, feldspar 0-10% and excluding 0 and quartz sand 70-95%. This method has the characteristics of simple structure and stable performance, and effectively overcomes the shortcomings of artificial core pore throat distribution, wettability and other differences from natural cores. However, the artificial core prepared by this method has not undergone the diagenetic process of first compaction and then cementation, which is quite different from the diagenesis of real samples, and a variety of chemical substances are added, which has poor inertness, complex components and unstable core properties.

[0007] Chinese patent CN112924260A discloses a calcareous cemented artificial core and its preparation method and application, including the following steps: 1) taking quartz sand of different particle sizes and mixing; 2) adding water to the quartz sand, and then adding calcium hydroxide powder to mix, to obtain a mixed system of quartz sand, water, and calcium hydroxide; 3) adding the mixed system to the core mold, pressurizing and compacting, and obtaining a compacted sample; 4) loading the compacted sample into a reactor, introducing carbon dioxide gas to react, and then drying it, repeating the above reaction at least once, to obtain a reacted sample; 5) drying the reacted sample, that is, obtaining a calcareous cemented artificial core. This method can truly simulate the compaction and cementation diagenesis in the process of rock diagenesis, and can meet the requirements of rock physical and chemical characteristics testing. However, this method only uses quartz sand and calcium hydroxide powder as experimental raw materials, and cannot obtain the temperature, pressure and pH value of the rock sample reaction process and the gas and liquid content finally involved in the reaction in real time. Therefore, it is difficult to approach the real core composition to a certain extent.

[0008] In summary, although predecessors have conducted a lot of research on the production of artificial sandstone cores, the existing artificial core preparation technology still has the following problems: 1. The equipment for preparing artificial cores is too simple, such as only using a hydraulic jack to apply pressure to press and form, or it is too complicated or expensive, such as using a high-temperature and high-pressure reactor; 2. The artificial cores produced have not undergone a diagenetic process of first compaction and then cementation, which is quite different from the diagenesis of real samples, and a variety of chemical substances are added, the inertness is poor, the composition is too complex, and the core properties are unstable; 3. The production process of artificial cores is inconsistent with the composition, pore throat structure and mechanical properties of natural cores, which limits the research and development of uranium resource exploration and development technology. Summary of the invention

[0009] The main purpose of the present invention is to provide a method for preparing dense uranium-containing sandstone artificial cores, which has the advantages of simple production process and low economic cost, and the manufactured uranium-containing artificial cores have stable properties and diverse components, and the diagenesis, pore throat structure and mechanical properties are closer to natural cores, which can provide reliable help for studying the simulation of fluid flow mechanism in dense sandstone-type uranium ore reservoirs and the inversion of in-situ leaching mining process. Correspondingly, a device used to implement the preparation method is also proposed.

[0010] The technical solution adopted by the present invention is: A method for preparing a dense uranium-containing sandstone artificial core comprises the following steps: S1. After mixing quartz sand and feldspar of different particle sizes, clay, uranium-containing minerals and calcium hydroxide powder are added and mixed thoroughly; S2, spraying water on the mixed system obtained in S1 to wet it, to obtain a mixed system of water, quartz sand, feldspar, clay, uranium-containing minerals and calcium hydroxide, stirring and cooling to room temperature, and measuring the total weight, then the residual water content in the mixed system = total weight - total solid amount; S3, adding the mixed system obtained in S2 into a core mold with dual temperature and pressure control, raising the temperature by 100 ℃~300 ℃, and the pressure by 50 MPa~200 MPa, while injecting a small amount of preheated water into the core mold, maintaining constant temperature and pressure for 12 h~24 h, and obtaining a sample after water-rock reaction under compaction; S4, introducing carbon dioxide and hydrogen sulfide gas into the core mold at least three times in sequence to obtain a sample after gas-water-rock reaction under compaction, and collecting and measuring the amount of gas and liquid that do not participate in the reaction; S5, cooling and depressurizing, when the temperature and pressure drop to room temperature and normal pressure, drying the reacted sample, and measuring the amount of gas and liquid involved in the reaction, that is, the amount of gas involved in the reaction = the amount of injected gas - the amount of collected gas, the amount of liquid involved in the reaction = the amount of injected liquid + the remaining water content in the mixed system - the amount of collected liquid - the amount of liquid evaporated; S6. Collect data on the changes in pressure, temperature and pH value of the core in the core mold over time during the gas-water-rock reaction process, and evaluate whether the pressure, temperature and pH value of the reaction meet the diagenetic environment of the natural dense uranium-bearing sandstone in the study area. If not, adjust the pressure and temperature of step S3, and adjust the liquid injection amount of step S3 and the gas injection amount of S4 according to the calculated influence of the amount of liquid and gas involved in the reaction on the pH value, until the relative error of the pressure, temperature, pH value of the obtained artificial core and the measured porosity and permeability and the natural dense uranium-bearing sandstone is within 5%.

[0011] In the above scheme, in step S1, the weight percentage of each raw material component is: quartz sand 60-85%; feldspar 10-25%; clay 2-15%; uranium-containing minerals 0-3%, excluding 0; calcium hydroxide 2-5%; the sum of the weight percentages of the raw materials is 100%; wherein: The particle sizes of the quartz sand include 40-60 mesh, 60-80 mesh, 80-100 mesh, 100-150 mesh, 150-200 mesh and above 200 mesh; and the mass ratio of the quartz sand with particle sizes of 40-60 mesh, 60-80 mesh, 80-100 mesh, 100-150 mesh, 150-200 mesh and above 200 mesh is (1.5-2.5): (2.5-5.5): (3.2-5.5): (1.1-3.5): (1.2-1.8): 1; The particle sizes of the feldspar include 40-80 mesh, 80-120 mesh, 120-200 mesh and above 200 mesh; and the mass ratio of the feldspar with particle sizes of 40-80 mesh, 80-120 mesh, 120-200 mesh and above 200 mesh is (4.5-8.5): (3.2-6.5): (1.2-3.5): 1; The type of the feldspar is potassium feldspar or sodium feldspar, or both; The mineral types of the clay include kaolinite, illite, montmorillonite and chlorite, wherein the total weight percentage of kaolinite and illite is not less than 80%, and the total weight percentage of montmorillonite and chlorite is not more than 20%; The uranium-containing minerals include pitchblende, uraninite, uraninite, titanothite and thoronite, wherein the total weight percentage of pitchblende and uraninite is not less than 85%, and the total weight percentage of uraninite, uraninite and thoronite is not more than 15%.

[0012] In the above scheme, in step S1, the clay, uranium-containing mineral and calcium hydroxide powder are added to the mixed system of quartz sand and feldspar in 5 to 10 times, and are fully stirred for 2 min to 5 min each time, and the total stirring time is not less than 30 min, so that the clay, uranium-containing mineral and calcium hydroxide powder are evenly attached to the surface of the mixed system of quartz sand and feldspar, and then cooled to room temperature.

[0013] In the above scheme, in step S2, the water used to moisten the mixed system is distilled water or groundwater.

[0014] In the above scheme, in step S3, the temperature and pressure increase process is as follows: the initial pressure is 5 MPa, the initial temperature is 20°C~30°C, and the pressure is gradually increased to 50MPa~200MPa with an increment of 10 MPa, and the heating rate is 20°C / hour to 100°C~300°C, ensuring that the pressure and temperature reach the preset values ​​at the same time. During the temperature and pressure increase process, water is injected into the core mold at a rate of 0~10ml / min, and the temperature and pressure are stabilized within the final pressure and temperature range for 12 h~24 h.

[0015] In the above scheme, the core mold used in step S3 includes a mold barrel, a mold upper cover, a mold lower cover, a loading rod, a liquid injection pipe joint, a gas injection pipe joint, a gas-liquid outflow pipe joint and a heating film; the mold upper cover and the mold lower cover are respectively installed on the upper end and the lower end of the mold barrel in a detachable manner, and a sample cavity is formed in the middle; the upper end of the loading rod is connected to the universal tensile testing machine, and the lower end of the loading rod passes through the mold upper cover and is slidably sealed and connected to the inner wall of the mold barrel, and the rock sample is axially compacted by the loading rod; the upper end of the loading rod is installed with a liquid injection pipe joint and a gas injection pipe joint. The liquid injection pipe joint and the gas injection pipe joint are connected with the sample cavity through a pipeline passed through the mold upper cover, water is injected into the sample cavity through the liquid injection pipe joint, and carbon dioxide and hydrogen sulfide gas are introduced into the sample cavity through the gas pipe joint; a gas-liquid outflow pipe joint is installed on the outer side of the mold lower cover, the gas-liquid outflow pipe joint is connected with the sample cavity through a pipeline passed through the mold lower cover, and the liquid and gas after the reaction in the sample cavity are discharged through the gas-liquid outflow pipe joint; the heating film is coated on the periphery of the mold cylinder to control the temperature in the sample cavity.

[0016] In the above scheme, step S3 uses a liquid injection system to inject water into the core mold, and the liquid injection system includes a first measuring cylinder, a constant speed and constant pressure fluid metering pump, an intermediate pressure vessel and a preheater. The inlet of the constant speed and constant pressure fluid metering pump is connected to the first measuring cylinder, and the outlet is connected to the inlet of the intermediate pressure vessel, the outlet of the intermediate pressure vessel is connected to the preheater, and the outlet of the preheater is connected to the inside of the core mold; the first measuring cylinder is placed on a first electronic balance.

[0017] In the above scheme, in step S4, the initial pressure of the carbon dioxide and hydrogen sulfide gas is 0.1-0.5 MPa, and the pressure is increased to 1 MPa at a rate of 0.2 MPa / h, and the reaction is repeated 3-6 times, and the total gas supply time is 12-24 h.

[0018] In the above scheme, step S4 uses a gas injection system to introduce carbon dioxide and hydrogen sulfide gas into the core mold. The gas injection system includes a CO2 gas cylinder, an H2S gas cylinder and a gas flow controller. The CO2 gas cylinder and the H2S gas cylinder are respectively connected to the gas supply main through branch pipelines. The branch pipelines are respectively provided with a pressure regulating valve and a pressure gauge. The gas flow controller is arranged on the gas supply main, and the gas supply main is connected to the inside of the core mold.

[0019] In the above scheme, step S4 uses a gas-liquid collection and metering system to measure the unreacted liquid and gas, and the gas-liquid collection and metering system includes a gas-liquid separator, a desiccant, a gas flow meter, a second measuring cylinder and a second electronic balance. The outlet of the core mold is connected to the gas-liquid separator, and the gas outlet of the gas-liquid separator is connected to the desiccant and the gas flow meter in sequence. The liquid outlet of the gas-liquid separator is connected to the second measuring cylinder, and the second measuring cylinder is placed on the second electronic balance.

[0020] In the above scheme, in step S5, the rate of the temperature reduction and pressure reduction process is ensured to be consistent with the rate of the temperature increase and pressure increase process, and the drying time is 10 to 24 hours.

[0021] In the above scheme, in step S6, a data acquisition system is used to collect data on the changes in pressure, temperature and pH value of the core in the core mold over time during the gas-water-rock reaction process. The data acquisition system includes a pressure sensor, a temperature sensor and a pH sensor pre-buried in the inner wall of the core mold, and a computer connected to each sensor for signal.

[0022] Correspondingly, the present invention also proposes a preparation device for a dense uranium-containing sandstone artificial core, which is used to implement the above-mentioned preparation method, and the preparation device includes a core mold, a liquid injection system, a gas injection system, a gas-liquid collection and metering system, and a data acquisition control system; The core mold comprises a mold barrel, a mold upper cover, a mold lower cover, a loading rod, a liquid injection pipe joint, a gas injection pipe joint, a gas-liquid outflow pipe joint and a heating film; the mold upper cover and the mold lower cover are respectively installed on the upper end and the lower end of the mold barrel in a detachable manner, and a sample cavity is formed in the middle; the upper end of the loading rod is connected to a universal tensile testing machine, and the lower end of the loading rod passes through the mold upper cover and is slidably and sealedly connected to the inner wall of the mold barrel, and the rock sample is axially compacted by the loading rod; the upper end of the loading rod is installed with a liquid injection pipe joint and a gas injection pipe joint The liquid injection pipe joint and the gas injection pipe joint are connected with the sample cavity through a pipeline penetrating the mold upper cover, water is injected into the sample cavity through the liquid injection pipe joint, and carbon dioxide and hydrogen sulfide gas are introduced into the sample cavity through the gas pipe joint; a gas-liquid outflow pipe joint is installed on the outer side of the mold lower cover, the gas-liquid outflow pipe joint is connected with the sample cavity through a pipeline penetrating the mold lower cover, and the liquid and gas after the reaction in the sample cavity are discharged through the gas-liquid outflow pipe joint; the heating film is coated on the periphery of the mold cylinder to control the temperature in the sample cavity; The liquid injection system comprises a first measuring cylinder, a constant speed and constant pressure fluid metering pump, an intermediate pressure container and a preheater, wherein the inlet of the constant speed and constant pressure fluid metering pump is connected to the first measuring cylinder, the outlet is connected to the inlet of the intermediate pressure container, the outlet of the intermediate pressure container is connected to the preheater, and the outlet of the preheater is connected to the liquid injection pipe joint of the core mold; The gas injection system includes a CO2 gas cylinder, an H2S gas cylinder and a gas flow controller, the CO2 gas cylinder and the H2S gas cylinder are respectively connected to the gas supply main pipe through branch pipelines, the branch pipelines are respectively provided with a pressure regulating valve and a pressure gauge, the gas flow controller is arranged on the gas supply main pipe, and the gas supply main pipe is connected to the gas injection pipe joint of the core mold; The gas-liquid collection and metering system comprises a gas-liquid separator, a desiccant, a gas flow meter, a second measuring cylinder and a second electronic balance, the gas-liquid outflow pipe joint of the core mold is connected to the gas-liquid separator, the gas outlet of the gas-liquid separator is connected to the desiccant and the gas flow meter in sequence, the liquid outlet of the gas-liquid separator is connected to the second measuring cylinder, and the second measuring cylinder is placed on the second electronic balance; The data acquisition system comprises a pressure sensor, a temperature sensor and a pH sensor which are pre-buried in the inner wall of the core mold, and a computer which is connected with the sensors by signals.

[0023] The beneficial effects produced by the present invention are: The method for preparing dense uranium-containing sandstone artificial cores provided by the present invention can realistically simulate the process of hydrothermal fluid injection during the diagenesis of uranium-containing sandstone, as well as the sedimentation compaction, cementation, replacement and dissolution diagenesis; and can regulate the physical property parameters of the generated artificial cores, including pH value, porosity and permeability, by feedback regulating the temperature, pressure and gas-liquid injection amount during the preparation process, thereby preparing dense uranium-containing sandstone artificial cores whose pH value, porosity and permeability all meet the requirements, and can be applied to the simulation of fluid flow mechanism in dense sandstone-type uranium ore reservoirs and the inversion of in-situ leaching mining process.

[0024] The sample preparation method of the present invention has low sample preparation cost and simple preparation process, and a plurality of samples can be prepared in a short time for experiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 It is a schematic flow chart of the method for preparing the dense uranium-containing sandstone artificial core of the present invention; Figure 2 It is a schematic structural diagram of a device for preparing a dense uranium-containing sandstone artificial core according to the present invention; Figure 3 yes Figure 2 A schematic diagram of the structure of a core mold of the preparation device shown; Figure 4 It is a schematic diagram of the appearance of the artificial uranium-containing sandstone core produced in Example 1 of the present invention.

[0027] In the figure: 1. core mold; 101. mold cylinder; 102. mold upper cover; 103. mold lower cover; 104. loading rod; 105. liquid injection pipe joint; 106. gas injection pipe joint; 107. gas-liquid outflow pipe joint; 108. heating film; 109. upper air permeable plate; 110. lower air permeable plate; 111. sealing ring; 112. guide ring; 113. rock sample; 114. temperature controller; 115. universal tensile testing machine; 2. Liquid injection system; 201. First measuring cylinder; 202. First electronic balance; 203. Constant speed and constant pressure fluid metering pump; 204. Pressure gauge; 205. Safety valve; 206. Intermediate pressure vessel; 207. Back pressure valve; 208. Temperature controller; 209. Preheater; 3. Gas injection system; 301. CO2 gas cylinder; 302. H2S gas cylinder; 303. Pressure regulating valve; 304. Pressure gauge; 305. Safety valve; 306. Gas flow controller; 4. Gas-liquid collection and metering system; 401. Safety valve; 402. Gas-liquid separator; 403. Desiccant; 404. Gas flow meter; 405. Second measuring cylinder; 406. Second electronic balance; 5. Data acquisition and control system; 501. Computer. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] It should be noted that the illustrations provided in the embodiments of the present invention are only used to illustrate the basic concept of the present invention in a schematic manner. Therefore, the drawings only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout type may also be more complicated.

[0030] In the present invention, it is also necessary to explain that, if the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc. appear, the orientation or position relationship indicated is based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, if the terms "first" and "second" appear, they are only used for description and distinction purposes, and cannot be understood as indicating or implying relative importance.

[0031] like Figure 1 As shown, the present invention proposes a method for preparing a dense uranium-containing sandstone artificial core, comprising the following steps: S1. After mixing quartz sand and feldspar of different particle sizes, clay, uranium-containing minerals and calcium hydroxide powder are added and mixed thoroughly.

[0032] S2. Spray water on the mixed system obtained in step S1 to wet it, so as to obtain a mixed system of water, quartz sand, feldspar, clay, uranium-containing minerals and calcium hydroxide; after stirring, cool it to room temperature, and measure the total weight, wherein the residual water content in the mixed system = total weight - total solid amount (the total amount of mineral components added in step S1).

[0033] S3. Add the mixed system obtained in S2 into a core mold with dual temperature and pressure control, increase the temperature by 100 ℃~300 ℃, and increase the pressure by 50 MPa~200 MPa. At the same time, inject a small amount of water into the core mold. Maintain the constant temperature and pressure for 12 h~24 h to obtain a sample after water-rock reaction under compaction.

[0034] In this step, the purpose of increasing temperature and pressure is to simulate the rock diagenesis process. The final temperature and pressure are proportional to the required burial depth of the sample. A certain period of constant temperature and pressure ensures that the diagenesis reaction is fully carried out. The role of injecting water is to simulate the process of hydrothermal fluid injection.

[0035] S4. Introduce carbon dioxide and hydrogen sulfide gas into the core mold at least three times in sequence. After the first gas is injected, the entire system needs to be evacuated before the second gas is injected to obtain a sample after the gas-water-rock reaction under compaction, and collect and measure the amount of gas and liquid that do not participate in the reaction.

[0036] In this step, the purpose of introducing carbon dioxide gas is to react chemically with calcium hydroxide to form calcium carbonate precipitation to simulate the calcite cementation of uranium-containing sandstone; the purpose of introducing hydrogen sulfide gas is to react chemically with the minerals in the mixed system to form pyrite precipitation, which, on the one hand, simulates the formation of pyrite in the diagenesis process of uranium-containing sandstone, and on the other hand, promotes the formation of secondary uranium ores, such as hydro (asphalt) uranium ore, calcium uranium mica, potassium vanadium uranium ore, etc., at the edge of pyrite. The above reactions are mainly:

[0037] In particular, the introduction of carbon dioxide gas and hydrogen sulfide gas not only causes carbon dioxide to cement into calcium carbonate and hydrogen sulfide to react to form pyrite, but also causes some minerals in the rock sample to undergo replacement and dissolution under high temperature and high pressure, such as the dissolution of carbonates and feldspars, and the interlacing and replacement of feldspar by carbonates.

[0038] S5. Cool down and reduce pressure. When the temperature and pressure drop to room temperature and normal pressure, dry the reacted sample for 10-24 hours and measure the amount of gas and liquid involved in the reaction, that is, the amount of gas involved in the reaction = the amount of injected gas - the amount of collected gas, and the amount of liquid involved in the reaction = the amount of injected liquid + the remaining water content in the mixed system - the amount of collected liquid - the amount of liquid evaporated.

[0039] S6. Collect data on the changes in pressure, temperature and pH value of the core in the core mold over time during the gas-water-rock reaction process, and evaluate whether the pressure, temperature and pH value of the reaction meet the diagenetic environment of the natural dense uranium-bearing sandstone in the study area. If not, adjust the pressure and temperature of step S3 and step S4, and adjust the liquid injection amount of step S3 and the gas-liquid injection amount of step S4 according to the calculated influence of the amount of liquid and gas involved in the reaction on the pH value, until the relative error of the pressure, temperature, pH value of the obtained artificial core and the measured porosity and permeability and the natural dense uranium-bearing sandstone is within 5%.

[0040] Further optimization, in step S1, each raw material component is proportioned as much as possible based on the main mineral components of natural sandstone-type uranium ore, wherein the weight percentage of each raw material component is: quartz sand 60 ~ 85%; feldspar 10 ~ 25%; clay 2 ~ 15%; uranium-containing minerals 0 ~ 3%, excluding 0; calcium hydroxide 2 ~ 5%; the sum of the weight percentages of the raw materials is 100%. Wherein: The particle sizes of quartz sand include 40~60 mesh, 60~80 mesh, 80~100 mesh, 100~150 mesh, 150~200 mesh and above 200 mesh; and the mass ratio of quartz sand with particle sizes of 40~60 mesh, 60~80 mesh, 80~100 mesh, 100~150 mesh, 150~200 mesh and above 200 mesh is (1.5~2.5):(2.5~5.5):(3.2~5.5):(1.1~3.5):(1.2~1.8):1.

[0041] The particle sizes of feldspar include 40~80 mesh, 80~120 mesh, 120~200 mesh and above 200 mesh; and the mass ratio of feldspar with particle sizes of 40~80 mesh, 80~120 mesh, 120~200 mesh and above 200 mesh is (4.5~8.5):(3.2~6.5):(1.2~3.5):1.

[0042] The types of feldspar are potassium feldspar or sodium feldspar, or both.

[0043] The mineral types of clay include kaolinite, illite, montmorillonite and chlorite, among which the total weight percentage of kaolinite and illite is not less than 80%, and the total weight percentage of montmorillonite and chlorite is not more than 20%.

[0044] Uranium-containing minerals include pitchblende, uraninite, uraninite, titanothite and thoronite, among which the total weight percentage of pitchblende and uraninite is not less than 85%; the total weight percentage of uraninite, titanothite and thoronite is not more than 15%.

[0045] Further optimization, in step S1, clay, uranium-containing minerals and calcium hydroxide powder are added to the mixed system of quartz sand and feldspar in 5 to 10 times, and each time is fully stirred for 2 min to 5 min, and the total stirring time is not less than 30 min, so that the clay, uranium-containing minerals and calcium hydroxide powder are evenly attached to the surface of the mixed system of quartz sand and feldspar, and then cooled to room temperature.

[0046] Further optimization, in step S2, the water used to moisten the mixed system is distilled water or groundwater.

[0047] Further optimization, in step S3, the temperature and pressure increase process is as follows: the initial pressure is 5 MPa, the initial temperature is 20℃~30℃, and the pressure is gradually increased to 50MPa~200MPa with a 10 MPa increment, and the heating rate is 20℃ / hour to 100℃~300℃, ensuring that the pressure and temperature reach the preset value at the same time. During the temperature and pressure increase process, preheated water is injected into the core mold at a rate of 0~10ml / min to simulate the impact of the injection of hydrothermal fluid in the formation on the rock, and the temperature and pressure are stabilized for 12 h~24 h within the final pressure and temperature range to ensure that the sample is fully compacted. The entire temperature and pressure increase process is carried out in a core mold with dual temperature and pressure control. The water injection rate is controlled at 0~10ml / min. On the one hand, it prevents the excessively high flow rate of the injected liquid from damaging the surface of the rock sample, and on the other hand, a long period of low flow rate allows the thermal fluid to fully react with the rock sample.

[0048] For further optimization, before starting step S3, it is necessary to perform a degassing experiment on the sample in the core mold and vacuumize the entire process by using a vacuum pump to ensure that the test data is more realistic.

[0049] Further optimization, the core mold 1 used in step S3 includes a mold barrel 101, a mold upper cover 102, a mold lower cover 103, a loading rod 104, a liquid injection pipe joint 105, a gas injection pipe joint 106, a gas-liquid outflow pipe joint 107 and a heating film 108; the mold upper cover 102 and the mold lower cover 103 are respectively installed on the upper end and the lower end of the mold barrel 101 in a detachable manner, and a sample cavity is formed in the middle; the upper end of the loading rod 104 is connected to the universal tensile testing machine 115, and the lower end of the loading rod 104 passes through the mold upper cover 102 and is slidably sealed and connected to the inner wall of the mold barrel 101, and the rock sample 113 is axially compacted by the loading rod 104; a liquid injection pipe joint 105 is installed on the upper end of the loading rod 104. Inlet pipe joint 105 and gas injection pipe joint 106, liquid injection pipe joint 105 and gas injection pipe joint 106 are connected with the sample cavity through a pipeline penetrated in the mold upper cover 102, water is injected into the sample cavity through the liquid injection pipe joint 105, and carbon dioxide and hydrogen sulfide gas are introduced into the sample cavity through the gas pipe joint; a gas-liquid outflow pipe joint 107 is installed on the outer side of the mold lower cover 103, the gas-liquid outflow pipe joint 107 is connected with the sample cavity through a pipeline penetrated in the mold lower cover 103, and the liquid and gas after the reaction in the sample cavity are discharged through the gas-liquid outflow pipe joint 107; a heating film 108 is coated on the outer periphery of the mold cylinder 101, and the temperature in the sample cavity is controlled by a temperature controller 114.

[0050] Further optimization, the lower end surface of the loading rod 104 is installed with an upper air permeable plate 109, and the upper end surface of the mold lower cover 103 is installed with a lower air permeable plate 110 to prevent mineral particles from blocking the liquid injection pipe joint 105, the gas injection pipe joint 106, and the gas-liquid outflow pipe joint 107 during the compaction process. The error between the diameter of the upper air permeable plate 109 and the lower air permeable plate 110 and the inner diameter of the mold is as small as possible (for example, <1 mm), the apertures on the air permeable plate are evenly distributed, and the apertures of the air permeable plate are as small as possible (for example, <0.5 cm) to prevent deformation of the upper and lower bottoms of the rock sample and loss of the particle skeleton. In order to prevent deformation of the upper and lower bottoms of the rock sample and loss of the particle skeleton, filter paper with the same diameter as the upper and lower air permeable plates 110 can also be added or the rock sample can be pre-compacted in advance, and the pre-compacting pressure needs to be as small as possible (for example, <5MPa).

[0051] For further optimization, a guide ring 112 is installed on the upper end surface of the mold cover 102, and the loading rod 104 is inserted into the guide ring 112; a sealing ring 111 is also provided between the loading rod 104 and the mold cover 102.

[0052] Further optimization, step S3 uses a liquid injection system 2 to inject water into the core mold 1. The liquid injection system 2 includes a first measuring cylinder 201, a constant speed and constant pressure fluid metering pump 203, an intermediate pressure container 206 and a preheater 209. The first measuring cylinder 201 is placed on a first electronic balance 202. The constant speed and constant pressure fluid metering pump 203 is used to adjust the pressure and injection rate of the injected fluid. Its inlet is connected to the first measuring cylinder 201, and its outlet is connected to the inlet of the intermediate pressure container 206. The intermediate pressure container 206 is used to store the liquid medium injected in the experiment, and its outlet is connected to the preheater 209. The preheater 209 is used to preheat the injected fluid. The preheating temperature is controlled by a temperature controller 208. The outlet of the preheater 209 is connected to the inside of the core mold 1.

[0053] For further optimization, a sealing cover resistant to high temperature and high pressure is also provided on the outside of the core mold 1 to ensure that the test data is more authentic.

[0054] Further optimization, in step S4, the initial pressure of carbon dioxide and hydrogen sulfide gas is 0.1~0.5MPa, and the pressure is increased to 1 MPa at a rate of 0.2 MPa / h. The reaction is repeated 3~6 times, and the total gas supply time is 12~24 h to ensure that the prepared sample reacts more fully with carbon dioxide and hydrogen sulfide.

[0055] Further optimization, step S4 uses a gas injection system 3 to introduce carbon dioxide and hydrogen sulfide gas into the core mold 1, the gas injection system 3 includes a CO2 gas cylinder 301, an H2S gas cylinder 302 and a gas flow controller 306, the CO2 gas cylinder 301 and the H2S gas cylinder 302 are respectively connected to the gas supply main through branch pipelines, the branch pipelines are respectively provided with a pressure regulating valve 303 and a pressure gauge 304, the gas flow controller 306 is arranged on the gas supply main, the gas supply main is provided with a safety valve 305, and the gas supply main is connected to the inside of the core mold 1.

[0056] Further optimization, step S4 uses a gas-liquid collection and metering system 4 to measure the unreacted liquid and gas, the gas-liquid collection and metering system 4 includes a gas-liquid separator 402, a desiccant 403, a gas flow meter 404, a second measuring cylinder 405 and a second electronic balance 406, the outlet of the core mold 1 is connected to the gas-liquid separator 402 via a safety valve 401, the gas outlet of the gas-liquid separator 402 is connected to the desiccant 403 and the gas flow meter 404 in sequence, the liquid outlet of the gas-liquid separator 402 is connected to the second measuring cylinder 405, and the second measuring cylinder 405 is placed on the second electronic balance 406.

[0057] Further optimization, in step S5, ensure that the rate of the temperature reduction and pressure reduction process is consistent with the rate of the temperature increase and pressure increase process, in order to avoid the rapid drop in temperature and pressure from damaging the sample and to protect the integrity of the sample to the greatest extent.

[0058] Further optimization, in step S5, the drying time is 10 to 24 h.

[0059] Further optimization, in step S6, the data acquisition system 5 is used to monitor the data of the pressure, temperature and pH value of the core in the core mold 1 during the gas-water-rock reaction process. The data acquisition system 5 includes a pressure sensor, a temperature sensor and a pH sensor arranged on the inner wall of the core mold 1, and a computer 501 connected to the signals of each sensor. The measuring range of the pressure sensor includes 0-200 MPa, the measuring range of the temperature sensor includes room temperature to 300 ° C, and the measuring range of the pH sensor includes 0 to 14.00 pH, because the chemical reaction generated during the gas introduction process causes the pH of the entire system to change.

[0060] Further optimization, in step S3, step S4 to step S5, except for the injection ports for gas and liquid and the ports for collecting unreacted gas and liquid, there is no leakage of gas or liquid during the entire reaction process of the rock sample in the core mold 1, so as to ensure that the test data is more realistic.

[0061] like Figure 2 As shown, the present invention also proposes a preparation device for a dense uranium-containing sandstone artificial core, comprising a core mold 1, a liquid injection system 2, a gas injection system 3, a gas-liquid collection and metering system 4, and a data acquisition control system. The core mold 1 is used to obtain a dense uranium-containing sandstone artificial core after a high-temperature and high-pressure reaction of a mixed sandstone powder sample, the liquid injection system 2 and the gas injection system 3 are used to provide the liquid and gas required for the reaction, respectively, the gas-liquid collection and metering system 4 is used to collect and meter the amount of liquid and gas discharged from the core mold 1, and the data acquisition control system is used to realize the collection and monitoring of temperature, pressure and pH value during the reaction.

[0062] Core mold 1 Figure 3As shown, it includes a mold barrel 101, a mold upper cover 102, a mold lower cover 103, a loading rod 104, a liquid injection pipe joint 105, a gas injection pipe joint 106, a gas-liquid outflow pipe joint 107 and a heating film 108; the mold upper cover 102 and the mold lower cover 103 are respectively installed on the upper end and the lower end of the mold barrel 101 in a detachable manner, and a sample cavity is formed in the middle; the upper end of the loading rod 104 is connected to the universal tensile testing machine, and the lower end of the loading rod 104 passes through the mold upper cover 102 and is slidably sealed and connected to the inner wall of the mold barrel 101, and the rock sample is axially compacted by the loading rod 104; the upper end of the loading rod 104 is installed with a liquid injection pipe joint 105 and a gas injection pipe joint 106, and the liquid injection pipe joint 105 and the gas injection pipe joint 106 are installed. The liquid injection pipe joint 106 is connected to the sample cavity through a pipeline penetrated in the mold upper cover 102, water is injected into the sample cavity through the liquid injection pipe joint 105, and carbon dioxide and hydrogen sulfide gas are introduced into the sample cavity through the gas pipe joint; a gas-liquid outflow pipe joint 107 is installed on the outer side of the mold lower cover 103, and the gas-liquid outflow pipe joint 107 is connected to the sample cavity through a pipeline penetrated in the mold lower cover 103, and the reacted liquid and gas in the sample cavity are discharged through the gas-liquid outflow pipe joint 107; a heating film 108 is coated on the outer periphery of the mold cylinder 101, and is used to control the temperature in the sample cavity. The heating film 108 is connected to the temperature controller 114 signal, and the temperature control range is room temperature to 200°C, the temperature control accuracy is ±0.3°C, and the pressure resistance is better than 100 MPa.

[0063] The liquid injection system 2 includes a first measuring cylinder 201, a constant speed and constant pressure fluid metering pump 203, an intermediate pressure container 206 and a preheater 209. The inlet of the constant speed and constant pressure fluid metering pump 203 is connected to the first measuring cylinder 201, and the outlet is connected to the inlet of the intermediate pressure container 206 storing the injection fluid. The outlet of the intermediate pressure container 206 is connected to the preheater 209 for preheating the injection fluid, and the outlet of the preheater 209 is connected to the liquid injection pipe joint 105 of the core mold 1. The flow range of the constant speed and constant pressure fluid metering pump 203 is 0-90mL / min, and the maximum output pressure is better than 100MPa. A pressure gauge 204 and a safety valve 205 are provided on the pipeline between the constant speed and constant pressure fluid metering pump 203 and the intermediate pressure container 206; a back pressure valve 207 is provided on the pipeline after the intermediate pressure container 206.

[0064] The gas injection system 3 includes a CO2 gas cylinder, an H2S gas cylinder and a gas flow controller 306. The CO2 gas cylinder and the H2S gas cylinder are connected to the gas supply main through branch pipelines, respectively. A pressure regulating valve 303 and a pressure gauge 304 are respectively provided on the branch pipelines. The gas flow controller 306 is arranged on the gas supply main, and the gas supply main is connected to the gas injection pipe joint 106 of the core mold 1.

[0065] The gas-liquid collection and metering system 4 includes a gas-liquid separator 402, a desiccant 403, a gas flow meter 404, a second measuring cylinder 405 and a second electronic balance 406. The gas-liquid outflow pipe joint 107 of the core mold 1 is connected to the gas-liquid separator 402, the gas outlet of the gas-liquid separator 402 is connected to the desiccant 403 and the gas flow meter 404 in sequence, the liquid outlet of the gas-liquid separator 402 is connected to the second measuring cylinder 405, and the second measuring cylinder 405 is placed on the second electronic balance 406.

[0066] The data acquisition system 5 includes a pressure sensor, a temperature sensor and a pH sensor pre-buried in the inner wall of the core mold 1, and a computer connected to the sensors for signals.

[0067] It should be noted that the preparation device of dense uranium-containing sandstone artificial core needs to be resistant to strong acid and strong alkali, and the material in direct contact with the gas can be Hastelloy.

[0068] Embodiment 1: A method for preparing a dense uranium-containing sandstone artificial core comprises the following steps: S1. Mix quartz sand and feldspar of different particle sizes, then add clay, uranium-containing minerals and calcium hydroxide powder, and mix them thoroughly. Weigh 500g of quartz sand, the particle size ratio is: 40-60 mesh 100.05g (20.01%), 60-80 mesh 176.3g (35.26%), 80-100 mesh 87.55g (17.51%), 100-150 mesh 68.05g (13.61%), 150-200 mesh 50.5g (10.1%) and above 200 mesh 17.55g (3.51%); Weigh 150g of feldspar, including 100g of potassium feldspar and 50g of sodium feldspar; Weigh 20 g of clay, including 10 g of kaolinite, 6 g of illite, and 4 g of montmorillonite; Weigh 10 g of uranium-containing minerals from a uranium deposit in the Tuha Basin in Xinjiang; Weigh 30 g of calcium hydroxide powder.

[0069] S2. The mixed system obtained in S1 is moistened by spraying a small amount of water for 6 times to obtain a mixed system of water, quartz sand, feldspar, clay, uranium-containing minerals and calcium hydroxide. The system is fully stirred for 2 min to 5 min each time, and the total time is about 30 min. After stirring, the system is cooled to room temperature and the total weight at this time is 745.12 g. The remaining water content in the mixed system = total weight 745.12 g - total solid amount 710 g = 35.12 g.

[0070] S3. Add the mixed system obtained in S2 into the core mold 1 with dual temperature and pressure control, with an initial pressure of 5 MPa and an initial temperature of 22°C. Gradually increase the pressure to 50 MPa in steps of 10 MPa, and increase the temperature at a rate of 20°C / hour to 144°C. At the same time, inject 184.7 g of water into the core mold 1. Keep the reaction at constant temperature and pressure for 12 hours (no water is injected at this time) to obtain a sample after water-rock reaction under compaction.

[0071] S4, carbon dioxide and hydrogen sulfide gas are introduced into the core mold 1 successively, the initial pressure of carbon dioxide and hydrogen sulfide gas is 0.1MPa, and the pressure is increased to 1MPa at a rate of 0.2MPa / h, and the gas supply is continued for 4h, and the above reaction process is repeated 3 times; after the first gas is injected into the core mold 1 (here, carbon dioxide is injected first and then hydrogen sulfide is injected), the entire system needs to be evacuated before the second gas is injected. Finally, the total amount of carbon dioxide injected = 0.0149kg / h (obtained by the gas flow controller 306) * 4h (one gas supply time) * 3 (number of repetitions) = 0.1788kg, the amount of hydrogen sulfide injected = 0.0082kg / h (obtained by the gas flow controller 306) * 4h (one gas supply time) * 3 (number of repetitions) = 0.0984kg, and the sample after gas-water-rock reaction under compaction is obtained. The amount of carbon dioxide that does not participate in the reaction is collected and measured in the gas-liquid collection and metering system 4 = 0.0087 kg / h (obtained through the gas flow meter 404) * 4 h (gas supply time) * 3 (number of repetitions) = 0.1044 kg, the amount of hydrogen sulfide that does not participate in the reaction = 0.0072 kg / h (obtained through the gas flow meter 404) * 4 h (gas supply time) * 3 (number of repetitions) = 0.0864 kg, and the water content is 0.125 kg (obtained through the second electronic balance 406).

[0072] S5. Cool down and reduce the pressure while ensuring that the rate of the cooling and pressure reduction process is consistent with that of the heating and pressure increase process. When the temperature and pressure drop to room temperature and normal pressure, dry the reacted sample for 10 hours, collect the water on the outer sealing cover of the core mold 1, and calculate the evaporated water content to be 17.56 g (the total weight of the entire sealing cover before the reaction minus the total weight of the sealing cover after the reaction is the evaporated water content). Finally, the amount of gas and liquid participating in the reaction was measured, that is, the amount of carbon dioxide participating in the reaction = 0.1788kg injected gas amount - 0.1044kg collected gas amount = 0.0744kg, the amount of hydrogen sulfide participating in the reaction = 0.0984kg injected gas amount - 0.0864kg collected gas amount = 0.012kg, the water content participating in the reaction = 184.7g injected liquid amount + 35.12g residual water content in the mixed system - 125.4g collected liquid amount - 12.56g liquid evaporation amount = 81.86g, and the pH value of the rock sample after the reaction obtained by the pH sensor was 6.8, which was slightly acidic.

[0073] S6. Collect data on the changes in pressure, temperature and pH value of the core in the core mold 1 over time during the gas-water-rock reaction process, and evaluate whether the pressure, temperature and pH value of the reaction meet the natural dense uranium-containing sandstone diagenetic environment of the study area. If not, adjust the pressure and temperature of step S3 and step S4, and adjust the liquid injection amount of step S3 and the gas-liquid injection amount of step S4 according to the calculated influence of the amount of liquid and gas involved in the reaction on the pH value.

[0074] Before successfully obtaining the above-mentioned pressure, temperature and gas-liquid injection volume values ​​that meet the diagenetic environment and physical property parameters of the natural dense uranium-bearing sandstone in the study area (Note: the above descriptions are all data from the fifth test), the process of step S3 and step S4 has been repeated 4 times; for example, in the second repetition process, the pressure was increased to 50 MPa and the temperature was increased to 156°C, and finally 0.083 kg of carbon dioxide, 0.021 kg of hydrogen sulfide gas and 0.0766 kg of water were reacted to form a pH value of 7.6, a porosity of 7.4%, and a density of 2.7 g / cm 3 , permeability 1.7*10 -3 μm 2 The core samples, of which pH value, porosity and permeability are neutral to the physical properties of the rocks in the study area, with porosity of 9%-15% and permeability of 0.2-1.5.*10 -3 μm 2 The situation does not match.

[0075] Based on this, in the next few debugging (i.e., the 3rd, 4th and 5th time), the main mineral component ratio and the maximum pressure of step S3 are kept unchanged, the maximum temperature of step S3 is gradually reduced by about 4°C, the water injection in step S3 is gradually increased by about 10g, the carbon dioxide gas injection in step S4 is gradually increased by 2-6g, and the hydrogen sulfide gas injection is gradually reduced by 2-6g, so as to regulate the proportion of minerals (such as calcite) generated by gas participating in water-rock reaction. According to the above 5 times of regulation process, it is preliminarily found that, while keeping the main mineral component ratio and the maximum control pressure of the system unchanged, by appropriately lowering the temperature, increasing the injection liquid and reducing the amount of hydrogen sulfide gas (inhibiting the formation of new minerals), the porosity of the sample core can be appropriately improved, while increasing the amount of carbon dioxide (promoting the formation of new minerals) while increasing the injection liquid may cause the permeability of the rock sample to decrease. It can be seen that based on the present invention, the physical property parameters of the artificial core generated by the above pressure, temperature and gas-liquid injection process can be regulated.

[0076] Finally, after five adjustments, the pH value of the reaction formed by 0.0744kg of carbon dioxide, 0.012kg of hydrogen sulfide gas and 0.0819kg of water was 6.8, the porosity was 9%, and the density was 2.5g / cm 3 , permeability 1.05*10 -3 μm 2 Dense uranium-bearing artificial sandstone core samples, such as Figure 4 As shown. Figure 4 It can be seen that the samples produced by the present invention have complete appearance, uniform mineral distribution, high strength, and can better simulate natural dense uranium-containing artificial samples.

[0077] It should be pointed out that, according to the needs of implementation, the various steps / components described in this application can be split into more steps / components, and two or more steps / components or partial operations of steps / components can be combined into new steps / components to achieve the purpose of the present invention.

[0078] The order of execution of each step in the above embodiment does not mean the order of execution. The order of execution of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiment of the present application.

[0079] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A method for preparing a dense uranium-containing sandstone artificial core, characterized in that: The following steps are involved: S1. After mixing quartz sand and feldspar of different particle sizes, clay, uranium-containing minerals and calcium hydroxide powder are added and mixed thoroughly; S2, spraying water on the mixed system obtained in S1 to wet it, to obtain a mixed system of water, quartz sand, feldspar, clay, uranium-containing minerals and calcium hydroxide, stirring and cooling to room temperature, and measuring the total weight, then the residual water content in the mixed system = total weight - total solid amount; S3, adding the mixed system obtained in S2 into a core mold with dual temperature and pressure control, raising the temperature by 100 ℃~300 ℃, and the pressure by 50 MPa~200 MPa, while injecting a small amount of preheated water into the core mold, maintaining constant temperature and pressure for 12 h~24 h, and obtaining a sample after water-rock reaction under compaction; S4, introducing carbon dioxide and hydrogen sulfide gas into the core mold at least three times in sequence to obtain a sample after gas-water-rock reaction under compaction, and collecting and measuring the amount of gas and liquid that do not participate in the reaction; S5, cooling and depressurizing, when the temperature and pressure drop to room temperature and normal pressure, drying the reacted sample, and measuring the amount of gas and liquid involved in the reaction, that is, the amount of gas involved in the reaction = the amount of injected gas - the amount of collected gas, the amount of liquid involved in the reaction = the amount of injected liquid + the remaining water content in the mixed system - the amount of collected liquid - the amount of liquid evaporated; S6. Collect data on the changes in pressure, temperature and pH value of the core in the core mold over time during the gas-water-rock reaction process, and evaluate whether the pressure, temperature and pH value of the reaction meet the diagenetic environment of the natural dense uranium-bearing sandstone in the study area. If not, adjust the pressure and temperature of step S3, and adjust the liquid injection amount of step S3 and the gas injection amount of S4 according to the calculated influence of the amount of liquid and gas involved in the reaction on the pH value, until the relative error of the pressure, temperature, pH value of the obtained artificial core and the measured porosity and permeability and the natural dense uranium-bearing sandstone is within 5%.

2. The method for preparing a dense uranium-containing sandstone artificial core according to claim 1, characterized in that: In step S1, the weight percentages of the raw material components are: quartz sand 60-85%; feldspar 10-25%; clay 2-15%; uranium-containing minerals 0-3% and excluding 0; calcium hydroxide 2-5%; The sum of the weight percentages of the raw materials is 100%; among which: The particle sizes of the quartz sand include 40-60 mesh, 60-80 mesh, 80-100 mesh, 100-150 mesh, 150-200 mesh and above 200 mesh; and the mass ratio of the quartz sand with particle sizes of 40-60 mesh, 60-80 mesh, 80-100 mesh, 100-150 mesh, 150-200 mesh and above 200 mesh is (1.5-2.5): (2.5-5.5): (3.2-5.5): (1.1-3.5): (1.2-1.8): 1; The particle sizes of the feldspar include 40-80 mesh, 80-120 mesh, 120-200 mesh and above 200 mesh; and the mass ratio of the feldspar with particle sizes of 40-80 mesh, 80-120 mesh, 120-200 mesh and above 200 mesh is (4.5-8.5): (3.2-6.5): (1.2-3.5): 1; The type of the feldspar is potassium feldspar or sodium feldspar, or both; The mineral types of the clay include kaolinite, illite, montmorillonite and chlorite, wherein the total weight percentage of kaolinite and illite is not less than 80%, and the total weight percentage of montmorillonite and chlorite is not more than 20%; The uranium-containing minerals include pitchblende, uraninite, uraninite, titanothite and thoronite, wherein the total weight percentage of pitchblende and uraninite is not less than 85%, and the total weight percentage of uraninite, uraninite and thoronite is not more than 15%.

3. The method for preparing a dense uranium-containing sandstone artificial core according to claim 1, characterized in that: In step S1, the clay, uranium-containing mineral and calcium hydroxide powder are added to the mixed system of quartz sand and feldspar in 5 to 10 times, and are fully stirred for 2 min to 5 min each time, and the total stirring time is not less than 30 min, so that the clay, uranium-containing mineral and calcium hydroxide powder are evenly attached to the surface of the mixed system of quartz sand and feldspar, and then cooled to room temperature.

4. The method for preparing a dense uranium-containing sandstone artificial core according to claim 1, characterized in that: In step S3, the temperature and pressure increase process is as follows: the initial pressure is 5 MPa, the initial temperature is 20°C~30°C, and the pressure is gradually increased to 50MPa~200MPa with an increment of 10 MPa, and the heating rate is 20°C / hour to 100°C~300°C, ensuring that the pressure and temperature reach the preset values ​​at the same time. During the temperature and pressure increase process, water is injected into the core mold at a rate of 0~10ml / min, and the temperature and pressure are stabilized within the final pressure and temperature range for 12 h~24 h.

5. The method for preparing a dense uranium-containing sandstone artificial core according to claim 1, characterized in that: The core mold used in step S3 includes a mold barrel, a mold upper cover, a mold lower cover, a loading rod, a liquid injection pipe joint, a gas injection pipe joint, a gas-liquid outflow pipe joint and a heating film; the mold upper cover and the mold lower cover are respectively installed on the upper end and the lower end of the mold barrel in a detachable manner, and a sample cavity is formed in the middle; the upper end of the loading rod is connected to the universal tensile testing machine, and the lower end of the loading rod passes through the mold upper cover and is slidably sealed and connected to the inner wall of the mold barrel, and the rock sample is axially compacted by the loading rod; the upper end of the loading rod is installed with a liquid injection pipe joint and a gas injection pipe joint. Pipe joints, the liquid injection pipe joint and the gas injection pipe joint are connected with the sample cavity through a pipeline penetrated in the upper cover of the mold, water is injected into the sample cavity through the liquid injection pipe joint, and carbon dioxide and hydrogen sulfide gas are introduced into the sample cavity through the gas pipe joint; a gas-liquid outflow pipe joint is installed on the outer side of the lower cover of the mold, the gas-liquid outflow pipe joint is connected with the sample cavity through a pipeline penetrated in the lower cover of the mold, and the liquid and gas after the reaction in the sample cavity are discharged through the gas-liquid outflow pipe joint; the heating film is coated on the periphery of the mold cylinder to control the temperature in the sample cavity.

6. The method for preparing a dense uranium-containing sandstone artificial core according to claim 1, characterized in that: Step S3 uses a liquid injection system to inject water into the core mold, and the liquid injection system includes a first measuring cylinder, a constant speed and constant pressure fluid metering pump, an intermediate pressure vessel and a preheater. The inlet of the constant speed and constant pressure fluid metering pump is connected to the first measuring cylinder, and the outlet is connected to the inlet of the intermediate pressure vessel. The outlet of the intermediate pressure vessel is connected to the preheater, and the outlet of the preheater is connected to the inside of the core mold; the first measuring cylinder is placed on a first electronic balance.

7. The method for preparing a dense uranium-containing sandstone artificial core according to claim 1, characterized in that: In step S4, the initial pressure of the carbon dioxide and hydrogen sulfide gases is 0.1-0.5 MPa, and the pressure is increased to 1 MPa at a rate of 0.2 MPa / h. The reaction is repeated 3-6 times, and the total gas supply time is 12-24 h.

8. The method for preparing a dense uranium-containing sandstone artificial core according to claim 1, characterized in that: In step S4, a gas injection system is used to introduce carbon dioxide and hydrogen sulfide gas into the core mold. The gas injection system includes a CO2 gas cylinder, an H2S gas cylinder and a gas flow controller. The CO2 gas cylinder and the H2S gas cylinder are respectively connected to the gas supply main through branch pipelines. A pressure regulating valve and a pressure gauge are respectively provided on the branch pipelines. The gas flow controller is arranged on the gas supply main, and the gas supply main is connected to the inside of the core mold.

9. The method for preparing a dense uranium-containing sandstone artificial core according to claim 1, characterized in that: In step S4, a gas-liquid collection and metering system is used to meter the unreacted liquid and gas. The gas-liquid collection and metering system includes a gas-liquid separator, a desiccant, a gas flow meter, a second measuring cylinder and a second electronic balance. The outlet of the core mold is connected to the gas-liquid separator, and the gas outlet of the gas-liquid separator is connected to the desiccant and the gas flow meter in sequence. The liquid outlet of the gas-liquid separator is connected to the second measuring cylinder, and the second measuring cylinder is placed on the second electronic balance.

10. The method for preparing a dense uranium-containing sandstone artificial core according to claim 1, characterized in that: In step S5, the rate of the temperature reduction and pressure reduction process is ensured to be consistent with the rate of the temperature increase and pressure increase process, and the drying time is 10 to 24 hours.

11. The method for preparing a dense uranium-containing sandstone artificial core according to claim 1, characterized in that: In step S6, a data acquisition system is used to collect data on the changes in pressure, temperature and pH value of the core in the core mold over time during the gas-water-rock reaction process. The data acquisition system includes a pressure sensor, a temperature sensor and a pH sensor pre-buried in the inner wall of the core mold, and a computer connected to each sensor for signal.

12. A device for preparing dense uranium-containing sandstone artificial core, characterized in that: Used to implement the preparation method according to any one of claims 1 to 11, the preparation device comprises a core mold, a liquid injection system, a gas injection system, a gas-liquid collection and metering system, and a data acquisition control system; The core mold comprises a mold barrel, a mold upper cover, a mold lower cover, a loading rod, a liquid injection pipe joint, a gas injection pipe joint, a gas-liquid outflow pipe joint and a heating film; the mold upper cover and the mold lower cover are respectively installed on the upper end and the lower end of the mold barrel in a detachable manner, and a sample cavity is formed in the middle; the upper end of the loading rod is connected to a universal tensile testing machine, and the lower end of the loading rod passes through the mold upper cover and is slidably and sealedly connected to the inner wall of the mold barrel, and the rock sample is axially compacted by the loading rod; the upper end of the loading rod is installed with a liquid injection pipe joint and a gas injection pipe joint The liquid injection pipe joint and the gas injection pipe joint are connected with the sample cavity through a pipeline penetrating the mold upper cover, water is injected into the sample cavity through the liquid injection pipe joint, and carbon dioxide and hydrogen sulfide gas are introduced into the sample cavity through the gas pipe joint; a gas-liquid outflow pipe joint is installed on the outer side of the mold lower cover, the gas-liquid outflow pipe joint is connected with the sample cavity through a pipeline penetrating the mold lower cover, and the liquid and gas after the reaction in the sample cavity are discharged through the gas-liquid outflow pipe joint; the heating film is coated on the periphery of the mold cylinder to control the temperature in the sample cavity; The liquid injection system comprises a first measuring cylinder, a constant speed and constant pressure fluid metering pump, an intermediate pressure container and a preheater, wherein the inlet of the constant speed and constant pressure fluid metering pump is connected to the first measuring cylinder, the outlet is connected to the inlet of the intermediate pressure container, the outlet of the intermediate pressure container is connected to the preheater, and the outlet of the preheater is connected to the liquid injection pipe joint of the core mold; The gas injection system includes a CO2 gas cylinder, an H2S gas cylinder and a gas flow controller, the CO2 gas cylinder and the H2S gas cylinder are respectively connected to the gas supply main pipe through branch pipelines, the branch pipelines are respectively provided with a pressure regulating valve and a pressure gauge, the gas flow controller is arranged on the gas supply main pipe, and the gas supply main pipe is connected to the gas injection pipe joint of the core mold; The gas-liquid collection and metering system comprises a gas-liquid separator, a desiccant, a gas flow meter, a second measuring cylinder and a second electronic balance, the gas-liquid outflow pipe joint of the core mold is connected to the gas-liquid separator, the gas outlet of the gas-liquid separator is connected to the desiccant and the gas flow meter in sequence, the liquid outlet of the gas-liquid separator is connected to the second measuring cylinder, and the second measuring cylinder is placed on the second electronic balance; The data acquisition system comprises a pressure sensor, a temperature sensor and a pH sensor which are pre-buried in the inner wall of the core mold, and a computer which is connected with the sensors by signals.

Citation Information

Patent Citations

  • Artificial sandstone core, preparation method and use thereof

    CN103880384A

  • Preparation method of Guantao Formation shallow-stratum loosened oil-containing artificial sandstone core

    CN107144452A

  • Device and method for measuring parallel core foam flooding gas-phase shunt volume

    CN102865898A

  • Natural gas hydrate formation drilling simulator

    CN104500031A

  • General type non-adhesive artificial sandstone core

    CN104634638A

Cited By

  • Ellipsometry-based method and device for quantitatively characterizing surface wettability of oil shale

    CN122545320A